INJECTION OF RAMIPRIL INTO THE LATERAL VENTRICLE INTERFERES WITH THE DRINKING RESPONSE INDUCED BY PHARMACOLOGICAL AND NATURAL THIRST STIMULI - Saad, W. A.; Luiz, A. C.; Camargo, LAA; Menani, José Vanderlei [UNESP]; Renzi, Antonio [UNESP]; Silveira, JEN; Paulino, M. A. (Associação Brasileira de Divulgação Científica (ABRADIC), 1994)
We investigated the effects of ramipril, an angiotensin I-converting enzyme (ACE) inhibitor, on water intake by male Holtzman rats (250-300 g) with cannulae implanted into the lateral ventricle. Intracerebroventricular (icv) injection of ramipril (1 mu g/mu l) significantly reduced drinking in response to subcutaneous (sc) injection of isoprenaline (100 mu g/kg) from 8.49 +/- 0.69 to 2.96 +/- 0.36 ml/2 h, polyethyleneglycol (PEG) (30% w/v, 10 ml/kg) from 9.51 +/- 2.20 to 1.6 +/- 0.34 ml/2 h or water deprivation for 24 h from 12.61 +/- 0.83 to 5.10 +/- 1.37 ml/2 h. Ramipril had no effect on water intake induced by cellular dehydration produced by sc injection of hypertonic saline (2 M NaCl). These results are consistent with the hypothesis that ramipril acts as an ACE-blocking agent in the brain. The possibility that ramipril is transformed to ramiprilat, the active drug, by the brain is suggested.
Keywords: RAMIPRIL; CENTRAL NERVOUS SYSTEM; ANGIOTENSIN; WATER INTAKE